The hero and the crown ebook - McKinley, Robin (Damar, 2014)
An outcast princess must earn her birthright as a hero of the realm—in this “utterly engrossing” Newbery Medal–winning fantasy ( The New York Times ). Aerin is an outcast in her own father’s court, daughter of the foreign woman who, it was rumored, was a witch, and enchanted the king to marry her. She makes friends with her father’s lame, retired warhorse, Talat, and discovers an old, overlooked, and dangerously imprecise recipe for dragon-fire-proof ointment in a dusty corner of her father’s library. Two years, many canter circles to the left to strengthen Talat’s weak leg, and many burnt twigs (and a few fingers) secretly experimenting with the ointment recipe later, Aerin is present when someone comes from an outlying village to report a marauding dragon to the king. Aerin slips off alone to fetch her horse, her sword, and her fireproof ointment . . . But modern dragons, while formidable opponents fully capable of killing a human being, are small and accounted vermin. There is no honor in killing dragons. The great dragons are a tale out of ancient history. That is, until the day that the king is riding out at the head of an army. A weary man on an exhausted horse staggers into the courtyard where the king’s troop is assembled: “The Black Dragon has come . . . Maur, who has not been seen for generations, the last of the great dragons, great as a mountain. Maur has awakened.”